Design optimization of cable-equipped barrel vault structures using improved shuffled based Jaya algorithm. (February 2023) - Kaveh, Ali; Hosseini, Seyed Milad
Highlights: An optimization framework is proposed for the optimal design of cable-equipped barrel vaults. The optimization aims to minimize the total weight of cable-equipped barrel vaults and optimize the prestressing forces of the cables. Comparison with different algorithms is made for two examples of double-layer barrel vaults. IS-Jaya suggests results comparable or superior to other considered algorithms. For each double-layer barrel vault, a cable-equipped form is modeled and designed optimally. It is shown that the cable-equipped form of the barrel vault is more economical than its double-layer barrel vault form. Abstract: An optimization framework for the design optimization of the cable-equipped barrel vault space structures is proposed. This framework is implemented based on the SAP2000-OAPI feature and Improved Shuffled based Jaya (IS-Jaya) algorithm. A cable-equipped form for the double-layer barrel vault structures is proposed and designed optimally. IS-Jaya algorithm found results superior or comparable to other state-of-the-art metaheuristics. Results indicated that the cable-equipped barrel vault is more cost-effective than its non-equipped form.